A Comparative Surface Cleaning Study of Op Structure, an Op Art PMMA Sculpture by Michael Dillon. Issue 1 (2nd January 2023) - Angelova, Lora V.; Sofer, Gates; Bartoletti, Angelica; Ormsby, Bronwyn
ABSTRACT: The cleaning of a poly(methyl methacrylate) (PMMA) sculpture, Op Structure by Michael Dillon (1967, Tate Collection T03717), was undertaken as a case study during the NANORESTART project. Novel cleaning techniques, including microemulsions and gels, were evaluated and compared against more commonly used treatment methods on mock-ups created to broadly represent the conservation challenges presented by this artwork. The experimental design is presented, including the creation of mock-ups of a contemporary plastic work that required surface soil reduction and removal of two non-original labels with different pressure-sensitive adhesives. More than thirty cleaning systems were applied to soiled mock-ups and evaluated using a combination of imaging, instrumental analysis, and empirical observations. A summary of results, which reflect the decision-making process that led to the final treatment strategy, is presented. After extensive trials, surface cleaning was carried out using an aqueous surfactant-chelator solution applied with microfiber cloths; adhesive labels were removed with dilute water/propan-2-ol cotton poultices.